Features of Using Models Pspice Software (Моделювання, керування та інформаційні технології, 2023)
The paper notes the features of the input language of Pspice software package, methods of describing sentences of the input language, building own models of the studied object and using the models specified in the open library of this complex. Possible operating modes of the complex and methods of their effective use are described. The results obtained make it possible to carry out effective circuit and technical modeling and analysis of both known objects and newly created ones, while ensuring the economy of material and human resources